Lapita and the temporal geography of prehistory - Terrell, John Edward
Ambrose (this issue, above) and Sand (this issue, above) reported on Lapita in the specific, without being parochial in their concerns. This paper looks at the largest Lapita picture, but is itself in turn based on new reports in the specific, here from the coast of Papua New Guinea which is key for the relations in space, in time and in cultural affinity of whatever human it is that Lapita is.